Prevailing fears of student youth when studying at a high school - Kulesha-Liubinets, Мирослава (Psychosomatic Medicine and General Practice, 2018)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" Congress. It is dedicated to revailing fears of student youth when studying at a high school.